Thyroid Dysfunction from Antineoplastic Agents - Hamnvik, Ole-Petter Riksfjord (Oxford University Press, 2011)
Unlike cytotoxic agents that indiscriminately affect rapidly dividing cells, newer antineoplastic agents such as targeted therapies and immunotherapies are associated with thyroid dysfunction. These include tyrosine kinase inhibitors, bexarotene, radioiodine-based cancer therapies, denileukin diftitox, alemtuzumab, interferon-α, interleukin-2, ipilimumab, tremelimumab, thalidomide, and lenalidomide. Primary hypothyroidism is the most common side effect, although thyrotoxicosis and effects on thyroid-stimulating hormone secretion and thyroid hormone metabolism have also been described. Most agents cause thyroid dysfunction in 20%–50% of patients, although some have even higher rates. Despite this, physicians may overlook drug-induced thyroid dysfunction because of the complexity of the clinical picture in the cancer patient. Symptoms of hypothyroidism, such as fatigue, weakness, depression, memory loss, cold intolerance, and cardiovascular effects, may be incorrectly attributed to the primary disease or to the antineoplastic agent. Underdiagnosis of thyroid dysfunction can have important consequences for cancer patient management. At a minimum, the symptoms will adversely affect the patient’s quality of life. Alternatively, such symptoms can lead to dose reductions of potentially life-saving therapies. Hypothyroidism can also alter the kinetics and clearance of medications, which may lead to undesirable side effects. Thyrotoxicosis can be mistaken for sepsis or a nonendocrinologic drug side effect. In some patients, thyroid disease may indicate a higher likelihood of tumor response to the agent. Both hypothyroidism and thyrotoxicosis are easily diagnosed with inexpensive and specific tests. In many patients, particularly those with hypothyroidism, the treatment is straightforward. We therefore recommend routine testing for thyroid abnormalities in patients receiving these antineoplastic agents.